Vagabundos e criminosos: o trabalho como mecanismo de poder e índice de criminalização no discurso jurídico-penal de reinserção social dos apenados - Santos, Adriana Cabral dos (2016)
This study was a critical investigation of the configuration of discourse on work in the Brazilian criminal legal discourse. We problematized the discourse of an alleged reintegrative social function proposed by the criminal legal system and analyzed the role of such discourse in the core of disciplinary power strategies that impose on individuals the honest worker condition as a major criterion for their rehabilitation and return to society as citizens. This critique is our starting point to build the argument that discourse on work as it appears in current criminal legal texts operates more as a criminalization index of those who do not have a lawful occupation than a guarantee of legitimate social transit for convicts and recognition of their dignity. For this purpose, we used as corpus the main sources of Law, namely the Federal Constitution of 1988, the Penal Code, the Penal Execution Law, the Brazilian criminal doctrine and an extensive, more recent penal jurisprudence with regard to techniques of resocialization through work. This critical line enabled us to recognize complexity and plurality of discourses - antagonistic, at times - that build the world of work as portrayed in legal texts. We also sought reference in the discussion on the centrality of work as a formative category of the social being as well as theories that defend the non-centrality of work. Throughout our investigation, we sough to question the very condition of such centrality and to understand the ways in which it was possible to produce a legitimating discourse on work as a model of emancipatory social conduct defended and demanded by the Brazilian punitive system. In a context of precariousness, unemployment and flexibilization of the world of work in contemporary society, convicts hardly ever succeed to resume the identity of honest, hard-working citizens - and no longer offenders. In this context, we also questioned the formulation of a discourse that speaks about human labor as the essence of man and criticizes the Marxist vision that is based on work centrality, and we approached the concept of Michel Foucault, our theoretician of reference, who understands work more as a mechanism of power that promotes the individuals’ submission and adaptation to a goods-producing society than the natural activity of man. We ascribe our study to the field of questions that tackle the political conception of the body as subject to labor imposed as productive and political force. It is about the issue of political technology of individuals, a technology of power, as named by the French author. The intended analysis has not dismissed the material existence of labor relations but sought to discuss the validity of a discourse that considers work the main resource for convict rehabilitation and index for the recognition of dignity and honesty. The Foucauldian discourse analysis was the foundation for the investigation of our object, especially if we understand discourses as social practices with power to institute knowledge and produce truths.